A revolution in Chile. But where is it headed? - Leite, Pietro (Revista Avesso: Pensamento, Memória e Sociedade, 2020)
The following essay is an attempt to unify and contextualize much of the media coverage on Chile’s protest waves throughout the end of 2019. Information was drawn from Chilean, Brazilian, and international English-speaking publications. After establishing a coherent timeline and narrative to the protests, I set out to understand the composition and dynamics of the protests. Finally, I explore possible causes and precedents to the Chilean crisis in education, healthcare, pensions, poverty and inequality.